2006
DOI: 10.1002/cne.21179
|View full text |Cite
|
Sign up to set email alerts
|

The folate metabolic enzyme ALDH1L1 is restricted to the midline of the early CNS, suggesting a role in human neural tube defects

Abstract: Folate supplementation prevents up to 70% of human neural tube defects (NTDs), although the precise cellular and metabolic sites of action remain undefined. One possibility is that folate modulates the function of metabolic enzymes expressed in cellular populations involved in neural tube closure. Here we show that the folate metabolic enzyme ALDH1L1 is cell-specifically expressed in PAX3-negative radial glia at the midline of the neural tube during early murine embryogenesis. Midline restriction is not a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 60 publications
4
51
1
Order By: Relevance
“…One such gene that fit these criteria is the aldehyde dehydrogenase 1 family, member L1 (Aldh1L1) gene, also known as 10-formyltetrahydrofolate dehydrogenase (FDH) (Cook et al, 1991;Anthony and Heintz, 2007). ISH for this gene indicated that its mRNA is expressed throughout the CNS in a pattern consistent with pan-astrocyte expression (Fig.…”
Section: Aldh1l1 Is a New Astrocyte-specific Markermentioning
confidence: 99%
“…One such gene that fit these criteria is the aldehyde dehydrogenase 1 family, member L1 (Aldh1L1) gene, also known as 10-formyltetrahydrofolate dehydrogenase (FDH) (Cook et al, 1991;Anthony and Heintz, 2007). ISH for this gene indicated that its mRNA is expressed throughout the CNS in a pattern consistent with pan-astrocyte expression (Fig.…”
Section: Aldh1l1 Is a New Astrocyte-specific Markermentioning
confidence: 99%
“…Recently, the application of gene expression profiling to purified astrocyte populations (Cahoy et al 2008;Doyle et al 2008;Fu et al 2009;Rowitch and Kriegstein 2010) has revealed several potential new markers, such as the gene encoding the folate metabolic enzyme Aldh1L1 (Anthony and Heintz 2007;Cahoy et al 2008;Ballas et al 2009;. Iterative use of such approaches may yield better methods for isolating and analyzing developing and mature astrocytes.…”
Section: Limitations and Caveats Of Currently Available Astrocyte Marmentioning
confidence: 99%
“…The GENSAT project (http://www.gensat. org/index.html) has also provided many new mouse strains that express the fluorescent marker green fluorescent protein (GFP) under the control of regulatory sequences that are specific to glial lineages, better enabling their identification in slice culture and in vivo (Anthony and Heintz, 2007).…”
Section: New Markers For Stage-specific Study Of the Oligodendrocyte mentioning
confidence: 99%